2015
DOI: 10.5194/acpd-15-25647-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing model and measured ice crystal concentrations in orographic clouds during the INUPIAQ campaign

Abstract: Abstract. This paper assesses the reasons for high ice number concentrations observed in orographic clouds by comparing in-situ measurements from the Ice NUcleation Process Investigation And Quantification field campaign (INUPIAQ) at Jungfraujoch, Switzerland (3570 m a.s.l.) with the Weather Research and Forecasting model (WRF) simulations over real terrain surrounding Jungfraujoch. During the 2014 winter field campaign, between the 20 January and 28 February, the model simulations regularly underpredicted the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 90 publications
(160 reference statements)
0
9
0
Order By: Relevance
“…18). Thus, additional processes, i.e., ice-multiplication (Field et al, 2017) as well as surface and near-surface processes, have to contribute significantly to the ICNC. The contribution of ice crystals from the surface is on the order of several hundreds of ice crystals per liter, which is estimated from the measurements after 19:10 UTC on 4 February 2017.…”
Section: Origin Of Crystals Measured At Mountain-top Stationsmentioning
confidence: 99%
See 1 more Smart Citation
“…18). Thus, additional processes, i.e., ice-multiplication (Field et al, 2017) as well as surface and near-surface processes, have to contribute significantly to the ICNC. The contribution of ice crystals from the surface is on the order of several hundreds of ice crystals per liter, which is estimated from the measurements after 19:10 UTC on 4 February 2017.…”
Section: Origin Of Crystals Measured At Mountain-top Stationsmentioning
confidence: 99%
“…In situ measurements are important to further improve our understanding of the microphysical properties and fundamental processes of orographic MPCs (Baumgardner et al, 2011) and are frequently conducted at mountain-top research stations. Despite an improved understanding of the origin of ice crystals from nucleation (DeMott et al, 2010;Hoose and Möhler, 2012;Murray et al, 2012;Boose et al, 2016) and secondary ice-multiplication processes (Field et al, 2017), the source of most of the ice crystals observed at mountaintop stations and their impact on the development of the cloud remains an enigma (Lohmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…proteins, tryptophan and Nicotinamide adenine dinucleotide (NADH); the latter is related to cell metabolism) such that they can be discriminated from non-biological, non-fluorescent particles (Kaye et al, 2005). Due to detector sensitivity and background fluorescence within the WIBS-4 optical chamber, the fluorescence of aerosol with diameters D p < 0.8 µm cannot be accurately measured, and the counting efficiency decreases (Gabey et al, 2011). Therefore, the analysis presented here is limited to aerosols with diameters greater than 0.8 µm, unless otherwise stated.…”
Section: Instrumentation and Inletsmentioning
confidence: 99%
“…ice crystals from nucleation (DeMott et al, 2010;Hoose and Möhler, 2012;Murray et al, 2012;Boose et al, 2016) and secondary ice-multiplication processes (Field et al, 2017), the source of most of the ice crystals observed at mountaintop stations and their impact on the development of the cloud remains an enigma .…”
Section: Introductionmentioning
confidence: 99%